Ndarboy Genk Personal Branding Strategy in the Dynamics of Popular Javanese Music - Damayanti, Riska; Sinaga, Syahrul Syah (Universitas Negeri Semarang, 2025)
This study examines the personal branding strategy implemented by Ndarboy Genk, one of the prominent figures in the development of Javanese popular music. The purpose of this research is to describe how personal branding is constructed and to analyze its contribution to the public acceptance of Javanese music within a broader cultural context. The study employs a descriptive qualitative method, utilizing data collection techniques such as observation, documentation, and literature review. The findings reveal that Ndarboy Genk develops his personal image through the consistent use of the Javanese language, everyday narratives that resonate with audiences, and intensive engagement with fans. The utilization of digital platforms such as YouTube, Instagram, and TikTok further enhances his authenticity and expands his visibility. This personal branding strategy not only supports the sustainability of his career but also strengthens the position of Javanese music in the Indonesian music industry. The study highlights the significance of personal branding as a key factor for local musicians in preserving cultural identity while competing within the national music scene..